Analisis Pelaksanaan Program Aplikasi Kepul (Jual Beli SaAnalisis Pelaksanaan Program Aplikasi Kepul (Jual Beli Sampah) Dalam Upaya Meningkatkan Kesadaran Masyarakat terhadap Kesehatan Lingkungan Helvetia Kecamatan Sunggal Kabupaten Deli Serdang - Nanda, Meutia; Deviyanti, Dira; Ramadan, Novrizal; Nurhamidah, Nurhamidah; Nasution, Finka Huzairi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The waste problem is caused by several factors, one of which is the low awareness and concern of the community about waste. The Kepul application is a new breakthrough and innovation that exists as a forum to invite people to care more about health and environmental hygiene through optimizing the buying and selling of waste that can be recycled through the Kepul application. The purpose of this study was to find out the success of the kepul application program in increasing public awareness of environmental health. The method used in this research is to use a qualitative approach with descriptive methods and case study research designs and data collection techniques used are in-depth interviews, observation and documentation. The research results obtained are the realization of environmental hygiene and health and being able to increase public awareness through the kepul application program and being able to change people's mindset towards waste. It can be concluded that the kepul implementation team has succeeded in inviting the public to care more about the health and cleanliness of the environment through the kepul application in an effort to increase public awareness of environmental health. Keywords: Awareness, Environment, Health, Kepul, Garbage